Influence of cutting time and stubble height on regrowth capacity of Juncus effusus and Juncus conglomeratus. (28th August 2014) - Kaczmarek‐Derda, W; Folkestad, J; Helgheim, M; Netland, J; Solhaug, K A; Brandsæter, L O; Zwerger, Peter
Summary Infestation by Juncus effusus and Juncus conglomeratus causes a serious reduction in forage quality along the western coastline in Norway. Timing of treatments, for example cutting to reduce photosynthate return to the weeds, is crucial for successful and cost‐effective weed control. However, the effect may depend on changes in regrowth capacity over the growing season. A growth chamber experiment was conducted to investigate the effect of cutting time and stubble height on the regrowth capacity of J. effusus and J. conglomeratus from western and eastern Norway. Tussocks were collected from extensively managed pastures at 4‐ and 6‐week intervals in 2009 and 2010, respectively. The plants were potted, cut at 1 or 5 cm and exposed to three different temperatures (7.5, 12.5 and 17.5°C) in 2009 and to 17.5°C only in 2010. The regrowth ability was evaluated after 6 weeks by measuring stem number and dry biomass from old mowed and new shoots. Regrowth increased more with temperature for the eastern than for the western ecotype of J. effusus. Cutting to 1 cm stubble height gave substantially less regrowth than 5 cm cutting, both for dry biomass and number of shoots in both years. Regrowth varied significantly with date of cut and was lowest in late summer (mid‐July–August). This suggests that weeding strategies based on low cutting and mowing rush tussocks in late summer will be most effective, due to the low regrowth capacity.